Hybrid 2D nanostructures for mechanical reinforcement and thermal conductivity enhancement in polymer composites. (3rd May 2018) - Ribeiro, Hélio; Trigueiro, João P.C.; Owuor, Peter S.; Machado, Leonardo D.; Woellner, Cristiano F.; Pedrotti, Jairo J.; Jaques, Ygor M.; Kosolwattana, Suppanat; Chipara, Alin; Silva, Wellington M.; Silva, Carlos J.R.; Galvão, Douglas S.; et al.
Abstract: Hexagonal boron nitride (h-BN), graphene oxide (GO) and hybrid (GO/h-BN) nanosheets were employed as fillers in order to enhance the physical properties of the polymer matrix. Composites based in epoxy and these two-dimensional (2D) nanofillers were produced with different wt% and their microstructure, mechanical and thermal properties were investigated. Increases up to 140% in tensile strength, 177% in ultimate strain and 32% in elastic modulus were observed for the hybrid GO/h-BN composite with 0.5 wt% content. The hybrid nanofiller also contributed to the increase up to 142% on thermal conductivity with respect to the pure epoxy for GO/h-BN composite with 2.0 wt% content. Molecular dynamic simulation was used to predict the behavior of possible stacking arrangements between h-BN and GO nanosheets tensioned by normal and shear forces. The results showed that the hybrid GO/h-BN combination can prevent the re-stacking process of exfoliated layers, demonstrating the synergism between these nanostructures with the final effect of better dispersion in the composite material. The excellent thermal and mechanical performance of these hybrid composites engineered by the combination of different types of the 2D inorganic nanoparticles make them multifunctional candidates for advanced materials applications. Graphical abstract: Image 1